An insight into renal disease associated with infective endocarditis - Adeniyi, A.B.; Nel, J.D. (SA Heart Journal, 2017)
This review on renal involvement associated with infective endocarditis offers clinicians insight into the pathophysiology behind each major mechanism of the renal disease. It briefly discusses the treatment of the various forms of renal disease, and describes pitfalls in the management of endocarditis that may significantly worsen the renal outcome. A practical approach is provided, based on the timing of onset of the renal disease, the patient’s history, and the correct interpretation of various clinical and biochemical parameters.